(untitled) (Tintas: Quaderni di Letterature iberiche e iberoamericane, 2022)
This article emphasizes the psychological and physical suffering of the sick subject through the poetic writing of the Spanish psychiatrist Luis Miguel Iruela. Therefore, on the one hand, we will analyze through his poetic writing the psychopathological dimensions of the patient, that is, the diseases of the body and the spirit. And, on the other hand, we will evidence the ideological strategies used by the doctor/psychiatrist to facilitate his cure. For this work, we will use the theories of Karl Jaspers’ psychopathology and Sigmund Freud’s psychoanalysis, to understand the dimension of the pathological and psychological phenomenon of the patient, and the therapeutic practices or resistance to his illness. The interest of this article is to understand the forms of suffering suffered by the patient in the hospital.